2011
DOI: 10.1037/a0023334
|View full text |Cite
|
Sign up to set email alerts
|

Interpersonal pathoplasticity in individuals with generalized anxiety disorder.

Abstract: Recent theories of Generalized Anxiety Disorder (GAD) have emphasized interpersonal and personality functioning as important aspects of the disorder. The current paper examines heterogeneity in interpersonal problems in two studies of individuals with GAD (n = 47 and n = 83). Interpersonal subtypes were assessed using the Inventory of Interpersonal Problems (IIP-C; Alden, Wiggins, & Pincus, 1990). Across both studies, individuals with GAD exhibited heterogeneous interpersonal problems, and cluster analyses of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
110
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 121 publications
(128 citation statements)
references
References 70 publications
14
110
3
Order By: Relevance
“…Additionally, major depressive disorder had marked elevation. Previous studies have found that generalized anxiety disorder, on average, has an exploitable interpersonal style (Przeworski et al, 2011;Salzer et al, 2011Salzer et al, , 2008; our results may differ due to our diagnostic approach. Our results for major depression are consistent with sample averages from previous studies (Barrett and Barber, 2007;Dinger et al, 2015;Grosse Holtforth et al, 2014;Locke et al, 2016;Quilty et al, 2013;Stangier et al, 2006).…”
Section: Psychopathology and Interpersonal Problemscontrasting
confidence: 71%
See 1 more Smart Citation
“…Additionally, major depressive disorder had marked elevation. Previous studies have found that generalized anxiety disorder, on average, has an exploitable interpersonal style (Przeworski et al, 2011;Salzer et al, 2011Salzer et al, , 2008; our results may differ due to our diagnostic approach. Our results for major depression are consistent with sample averages from previous studies (Barrett and Barber, 2007;Dinger et al, 2015;Grosse Holtforth et al, 2014;Locke et al, 2016;Quilty et al, 2013;Stangier et al, 2006).…”
Section: Psychopathology and Interpersonal Problemscontrasting
confidence: 71%
“…Due to methodological and reporting limitations of many of these studies, conclusions regarding profile descriptors are difficult to draw. In general, these studies suggest that major depressive disorder has a nonassertive and socially avoidant style (Barrett and Barber, 2007;Dinger et al, 2015;Grosse Holtforth et al, 2014;Locke et al, 2016;Quilty et al, 2013;Stangier et al, 2006), social phobia has a nonassertive style (Cain et al, 2010;Kachin et al, 2001;Stangier et al, 2006), and generalized anxiety disorder has an exploitable style (Przeworski et al, 2011;Salzer et al, 2008Salzer et al, , 2011. These disorders also seem to have marked elevation.…”
Section: Introductionmentioning
confidence: 93%
“…A number of investigations have found that individual differences in interpersonal problems exhibit pathoplastic relationships with mental disorders (e.g., Kasoff & Pincus, 2002;Pincus & Borkovec, 1994;Przeworski et al, 2010;Salzer et al, 2008), pathological symptoms (e.g., Ambwani & Hopwood, 2009;Hopwood, Clarke, & Perez, 2007), and maladaptive traits (e.g., Slaney, Pincus, Uliaszek, & Wang, 2006;Wright, Pincus, Conroy, & Elliot, 2009). For example, Kachin et al (2001) examined interpersonal pathoplasticity in 60 undergraduates diagnosed with social phobia using the Anxiety Disorders Interview Schedule-IV (Brown, DiNardo, & Barlow, 1994).…”
Section: Pathoplasticitymentioning
confidence: 99%
“…For instance, dimensional worry, as well as clinical and subthreshold symptoms of generalized anxiety disorder (GAD), predicted distress about social relationships (Breitholtz, Johansson, & Öst, 1999;Roemer, Molina, & Borkovec, 1997) and interpersonal difficulties (Erickson & Newman, 2007;Przeworski et al, 2011;Ruscio et al, 2005). Clinical and subthreshold social anxiety symptoms (e.g., fear of negative evaluation) also predicted interpersonal dysfunction (Alden & Phillips, 1990;Carleton, Collimore, & Asmundson, 2010;Davila & Beck, 2002;Kachin, Newman, & Pincus, 2001;Rapee & Heimberg, 1997;Wenzel, Graff-Dolezal, Macho, & Brendle, 2005) as have clinical, subthreshold, and remitted levels of depressive symptoms (Hammen & Brennan, 2002;Stewart et al, 2002).…”
mentioning
confidence: 99%
“…Measuring all combinations of these dimensions ensures that specific types of problems are not overlooked (e.g., trusting and forgiving too much reflects a combination of high affiliation and low dominance). IPC research has linked selfreported interpersonal problems of many types to the aforementioned symptoms (e.g., Cain, Pincus, & Grosse Holtforth, 2010;McEvoy et al, 2013;Przeworski et al, 2011).…”
mentioning
confidence: 99%